Association between virulence factors and biofilm formation in Enterococcus faecalis isolated from semen of infertile men. (29th May 2022) - Shahroodian, Soheila; Mirshekar, Maryam; Talebi, Malihe; Torki, Alireza; Amirmozafari, Nour
Abstract: Problem: Enterococcus faecalis is a common microbial semen contaminant. Although virulence factors and biofilm formation have often been analyzed in Enterococcus spp., there is little information about these features in isolates obtained from the genitourinary tract. This study was intended to characterize and determine the relationship between biofilm‐forming ability and the presence of E. faecalis virulence factors isolated from human semen. Method of study: A total of 32 patients diagnosed with primary infertility and 28 healthy men were included in the study. Semen analyses were performed according to the WHO guidelines. PCR reactions were applied for the detection of ace, esp, efeA, gelE, asa 1, and cyl A genes. Microtiter plate assay, via measurement of OD560, was used to measure the biofilm‐forming ability of the isolates. Results: Sixty E. faecalis isolates from semen of infertile and fertile men were characterized by phenotypic and genotypic methods. The prevalence of ace, esp, efe A, gel E, asa 1 and cyl A were reported to be 81.3%/100.0%, 81.3%/89.3%, 81.3%/85.7%, 71.9%/53.6%, 8.8%/75.0%, and 62.5%/67.9% in infertile/fertile groups; respectively. Strong, weak, and non‐biofilm reactions were reported to be 50.0%/21.4%, 40.6%/64.3%, and 9.4%/14.3% in infertile and fertile groups; respectively. Conclusions: There was a significant relationship between fertility and weak biofilm reaction and also between biofilm formation and possession of the esp gene ( P < .05). It could be speculated that colonization with E. faecalis with a strong ability for biofilm formation could become a potential threat to men's fertility.